Quantitation of immunoglobulin mu-gamma 1 heavy chain switch region recombination by a digestion-circularization polymerase chain reaction method. - Chu, C C (1992)
B lymphocytes expressing surface IgM with or without IgD may switch to the expression of other isotypes (IgG, IgA, or IgE) in the course of immune responses. Analyses of genomic DNA from cloned myelomas and hybridomas have shown that the isotype switch is accompanied by a rearrangement characterized by deletion of DNA between the switch (S) region of the mu gene and that associated with the new isotype, resulting in the formation of a composite S region. Measurement of this deletional rearrangement has been difficult in populations of normal B cells but would be useful for investigating the mechanism of the rearrangement and determining whether deletional rearrangement is responsible for all instances of class switching. We have developed a sensitive assay for deletional rearrangement that we designate the digestion-circularization polymerase chain reaction (PCR). In this assay, genomic DNA is digested with a restriction enzyme that recognizes sites that flank the recombined composite S region. The digested DNA is then ligated at low concentrations to favor the formation of circles. The ligation joins the 5' and 3' ends of each restriction fragment, making it possible to amplify by PCR across the ligated restriction site by using appropriate primers. From DNA that has undergone deletional rearrangement, a single-sized PCR product is produced and can be quantitated. We demonstrate here that the digestion-circularization PCR assay can detect S mu-S gamma 1 rearrangements in B cells cultured with lipopolysaccharide and interleukin 4. The assay is sensitive enough to quantitate switched cells constituting only 1-2% of the population.